The Quality of Physic Nut (Jatropha curcas) Seeds Affected by Water Activity and Duration of Storage - OKKY SETYAWATI DHARMAPUTRA; RANTJE LILLY WORANG; RIZAL SYARIEF; . MIFTAHUDIN (Indonesian Society for microbiology, 2009)
The quality of physic nut (Jatropha curcas) seeds should be maintained during storage, either as seeds for seedlings or oil production to be used for biodiesel. The effects of water activity and duration of storage on the quality, i.e. fungal population, lipid, fatty acid and free fatty acid contents, and viability of physic nut seeds were investigated. The results showed that the moisture content of seeds and total fungal population decreased at low water activities, and increased at high water activities (aw). At aw 0.64, at the beginning of storage and after 20 weeks of storage, total fungal populations were 5.4 x 103 and 1.8 x 102 cfu g-1 dry basis (db), respectively. At aw 0.93, at the beginning of storage and after 20 weeks of storage, total fungal populations were 5.0 x 103 and 3.3 x 106 cfu g-1 db, respectively. At the beginning of storage fungi infecting seeds were field fungi, i.e. Cladosporium sp., Colletotrichum sp., Fusarium semitectum, and F. verticillioides. The population of field fungi decreased with the increase of storage duration. They were replaced by postharvest fungi, i.e. Aspergillus restrictus, A. penicillioides, Eurotium chevalieri, E. rubrum, Penicillium citrinum, P. implicatum and P. oxalicum. Lipid content and viability of seeds decreased with the increase of water activities and seed moisture contents, while free fatty acid contents increased with the increase of water activities and seed moisture contents during storage. Fatty acids of lipid were dominated by unsaturated fatty acids, i.e. oleic and linoleic acids. Physic nut seeds could be stored at aw 0.64-0.75 up to eight weeks when the seeds will be used for seedling, or up to 16 weeks when they will be used for producing oil.